Stakeholder Engagement for Rebuilding Tourism - Paluseri, A. Risdawati Alwi; Imron, Dian Karinawati; Oktarina, Adelia; Fazri, Muhammad; Pertiwi, Cita; Nababan, Febrina Elia; Roidatua, Marthella Rivera (Masyarakat Indonesia, 2022)
The impact of the pandemic on the tourism sector had led to the paralyzed activities of people who depend on tourism. Bali communities with their tourism strength display how their skills that linked to tourism were challenged by the pandemic situation. Their capabilities in the service sector were not sufficient to overcome the challenges. Initiations arisen from community networks to solve the problems have been conducted through upskilling. A learning community adapts and improves the skills that need to be mastered in the new tourism era. This article aims to analyze how community networks encourage upskilling as a solution through a stakeholder engagement approach employingcase studies as the analytical method. Authors conducted research of the existing issues and found patterns from examples of villages that carried out upskilling activities. Findings show that the stakeholders engagement approach starts from the stakeholders mapping and they have roles in generating partnership action strategy. In addition, such activities enhance the awareness of the significant roles of stakeholders who are directly involved in those communities actions.